1954
DOI: 10.1136/jcp.7.2.87
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Limitations of Filter-paper Electrophoresis

Abstract: In 1935 Tiselius, using the apparatus he had devised in 1930, demonstrated that human serum globulin fell into three reasonably defined groups based on their electrophoretic mobilities. For the next 15 years a steady flood of papers reported the fluctuations of albumin and the globulins in young and old, in health and disease, as disclosed by analyses carried out using Tiselius apparatus with and without the numerous minor modifications which were introduced.In spite of brilliant efforts at simplification it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1956
1956
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 125 publications
0
19
0
Order By: Relevance
“…Because of the ease with which fibrinogen becomes denatured (17,19,20) results may be fallaciously low as part of it may be left at the starting line. Furthermore, spuriously high results may be obtained because of the formation of an abnormally dense band, as shown in figure lb.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Because of the ease with which fibrinogen becomes denatured (17,19,20) results may be fallaciously low as part of it may be left at the starting line. Furthermore, spuriously high results may be obtained because of the formation of an abnormally dense band, as shown in figure lb.…”
Section: Resultsmentioning
confidence: 98%
“…Finally, recognition of the numerous difficulties in the estimation of individual serum protein fractions (17,21,22,23,24) which would apply equally to the estimation of fibrinogen, has resulted in the general abandonment of the expression of results as absolute amounts, and they are now usually expressed as a percentage of the total dye absorbed under standard conditions. Although the standard methods of estimating fibrinogen are by no means free from error (25) they appear to be no more time-consuming and considerably more accurate than techniques using paper electrophoresis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Changes occurring in other diseases have been reported by Seibert and others (1947), Flynn (1954), Hardwicke (1954), and many others. Further, Martin and Franglen (1954) have shown that paper-strip electrophoresis cannot properly be used for quantitative analysis. Gilliland and others (1956) found that the albumin/a2 globulin ratio could be correlated with the activity of pulmonary tuberculosis, varying from 3.45 for patients with extensive active tuberculosis to 5.69 for those with arrested disease.…”
Section: Discussionmentioning
confidence: 99%
“…These workers attribute this effect to the formation of complexes between borate ions and a-glycol groups in the lipoid components of the a-globulins (Martin and Franglen, 1954 (1) paper-strip electrophoresis. It seems likely, however, that 83-globulin is the main source, with occasional and variable increments from the a-globulins depending upon the concentration and distribution of the associated lipids which are transferable to the new position.…”
Section: G a Lloyd And G T Stewartmentioning
confidence: 99%